Low threshold current density and high characteristic temperature narrow-stripe native oxide-confined 1.3-μm InGaAsN triple quantum well lasers - Liu, C. Y. (2013)
InGaAsN triple-quantum-well (TQW) 4-μm ridge waveguide (RWG) lasers were fabricated using pulsed anodic oxidation. High output power of 290 mW (both facets), low transparency current density of 389 A/cm2 (equivalent to 130 A/cm2/well) and high characteristic temperature (T0) of 157.2 K were obtained from the InGaAsN TQW RWG lasers. InGaAsN single-quantum-well (SQW) 4-μm RWG lasers were also fabricated for comparison. Extremely low threshold current (Ith) of 15.7 mA was obtained from InGaAsN SQW RWG laser (4 × 500 μm2). However, InGaAsN SQW laser showed strong temperature dependence of Ith and presented much lower T0 than that of InGaAsN TQW lasers. Ridge height effects on the T0 of RWG lasers were also demonstrated.